The Search for Islam by Walangsungsang (Study of Historical Manuscript Analysis) - Nuraidah, Syifa; Asep Achmad Hidayat; Thohir, Ajid; Supendi, Usman (Zona Education Indonesia, 2023)
This research focuses on a philological study aimed at unraveling and understanding the process of Walangsungsang's search for Islam, the main character in the manuscript "Lampahing Para Wali Kabeh." This manuscript holds significant historical and religious value in Javanese culture. The objective of this study is to analyze and interpret the philological context surrounding Walangsungsang's journey in comprehending Islam. The research methodology involves a critical analysis of the text of "Lampahing Para Wali Kabeh" and related historical sources. A philological approach is applied to comprehend Walangsungsang's role within the social, cultural, and religious context of the past. Textual and linguistic analyses are used to gain profound insights into the Islamic teachings presented in this manuscript. The findings reveal that Walangsungsang is a character on a quest for meaning and truth within Islam. His spiritual journey is reflected through the events he experiences and dialogues with the "Wali Kabeh" (The Enlightened Ones). The manuscript also portrays how Islamic teachings were conveyed within Javanese culture during that period. This philological study contributes to a deeper understanding of the process of Islam's adaptation and assimilation in Javanese society in the past. Additionally, this research provides insights into the role of literature in conveying religious messages and spiritual values to the present generation